AKUNTABILITAS KINERJA INSTANSI PEMERINTAH - Darwanis Darwanis; Sephi Chairunnisa (Program Magister Akuntansi Unsyiah, 2013)
This research aims to study was done in order to test : ( 1 ) the effect of the application areas of financial accounting , financial reporting quality control , and budget goal clarity on accountability Aceh government performance , ( 2 ) the effect of the application of financial accounting performance accountability of government to the regions of Aceh , ( 3 ) the effect on the financial statements of the quality control performance accountability Aceh government , ( 4 ) the influence of budget goal clarity on government performance accountability Aceh .The population in this study were all officials involved in financial processes, reporting and budget consisting of the Head of Division (Head ) and Reporting Program, Head of Section ( Kasi ) monitoring , evaluation and reporting , and the Head of Sub- section ( Kasubbag ) finances . The selection is done by using the population census methods, namely the method of election of the population used to examine all the elements that exist in the target area or researchThe results showed that the application of the area of financial accounting, financial reporting quality control , and clarity of the budget targets simultaneously affect the performance accountability of government agencies in Aceh . The application areas of financial accounting effect on performance accountability Aceh government agencies. Oversight of financial reporting quality effect on performance accountability of government agencies in Aceh . Budget goal clarity does not affect the performance accountability of government agencies in Aceh .Kata Kunci : Application of Regional Financial Accounting, Control of financial statement quality, Budget target Clarity , Performance Accountability